Building websites with XOOPS a step-by-step tutorial : get your XOOPS website up fast using this easy-to-follow guide - Atwal, Steve; Safari eBooks (Birmingham, U.K. : Packt Pub., 2006)
"If you want to create a powerful, fully-featured website in no time, this book is for you. This book will help you explore XOOPS, putting you in the picture of what it offers, and how to go about building a site with the system. You will be introduced to the main components of XOOPS, and learn how to manage them. You will develop the skills and confidence to manage all types of content on the site, and also understand how users interact with the site. As you find your way round, your own ideas for what you need in your new website begin to crystallize around what you can see of the capabilities and flexibility of XOOPS"--Resource description page.
Description based on print version record.
Includes index.
Keywords: Web site development; Open source software; Electronic books